Proses Berpikir Kreatif Siswa SMP dalam Menyelesaikan Masalah Matematika Open-Ended Ditinjau dari Kemampuan Matematika - Muhammad Aldi; Ismail Ismail (Program Studi S1 Matematika UNESA, 2023)
Future challenges that are increasingly complex require the competence of graduates who are not only skilled, but also creative. The process of creative thinking has four stages, namely synthesizing ideas, building ideas, planning the implementation of ideas, and implementing ideas. Open-ended math problems are a medium that teachers can use to find out students' creative thinking processes. The purpose of this research is to describe the process of creative thinking of junior high school students in solving open-ended math problems in terms of mathematical abilities. This research is a qualitative descriptive study conducted in 7th grade of SMP Muhammadiyah 2 Taman. The research subject was one student from each category of high, medium and low mathematical ability. Data collection methods used are test and interview methods. The results obtained were that at the stage of synthesizing ideas, subjects with high, medium, and low mathematical abilities did so based on experience in class with known formulas. At the stage of building ideas, subjects with high mathematical abilities considered convenience, subjects with mathematical abilities considered other ways, and subjects with low mathematical abilities considered logic. At the stage of planning the implementation of the idea of a high ability subject and is doing it smoothly and productively, the low math ability subject is doing it inefficiently. As well as at the stage of applying the idea, the subject of high mathematical ability fulfilled the creative thinking aspects of fluency, flexibility, and novelty, the subject of medium mathematical ability fulfilled the aspect of flexibility, and novelty, the subject of low mathematical ability only fulfilled the aspect of flexibility.